Promoting a Low-carbon Indonesia: How Energy Consumption and Financial Development Shape its Path - Farabi, Ahmad; Kurniadi, Anggi Putri; Salim, Zamroni; Ginta, Turnad Lenggo; Lenggogeni, Lenggogeni; Azka, Muizuddin; Saputra, Hens; Utomo, Setyo Margo; Nurmayni, Ratna; Islahudin, Nur (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of energy consumption (ENC) and financial development on environmental quality, measured by CO2 emissions in Indonesia. Financial development is represented by domestic credit to the private sector (CRD), international trade (ITR), and foreign direct investment (FDI). The ARDL methodology was selected as the most suitable approach based on the characteristics of the data. The findings reveal that, in the long term, all independent variables show a significantly negative effect on CO2 emissions, with CRD, ITR, and FDI contributing to emission reductions except ENC. However, ENC negatively affects CO2 emissions in the short term, whereas ITR and FDI show positive effects highlighting the importance of prioritizing energy efficiency and environmental considerations. This study is novel in its use of the latest data and its inclusion of several financial development variables namely domestic credit, trade, and investment.